Economic Exploitation of Pakistani Women: A Marxist Feminist Analysis of How to Get Filthy Rich in Rising Asia - Shaukat Ali; Muhammad Tufail Chandio (University of Chitral Journal of Linguistics and Literature, 2024)
This study critically examines the structural, gendered, and class-based modalities of female economic exploitation in Mohsin Hamid’s How to Get Filthy Rich in Rising Asia, drawing on Tithi Bhattacharya’s Social Reproduction Theory (SRT) within a Marxist feminist framework. It explores how the seemingly individualized narrative of upward mobility in the Global South relies on the collective, often invisible labor of women. Through close textual analysis, the roles of the protagonist’s mother, sister, and the “pretty girl” are examined to reveal how their paid and unpaid labor—domestic, emotional, reproductive, and sexual—constitutes the unseen foundation of the male protagonist’s capitalist ascent. Situating the novel within the socio-economic and patriarchal context of South Asia, the study demonstrates how women’s bodies, time, and roles are commodified and appropriated to sustain neoliberal development. By synthesizing Marxist feminist theory and hermeneutic analysis, the paper positions literature as a socio-economic artefact that reflects and reinforces dominant ideologies. It concludes that postcolonial capitalist success is inseparable from the systemic exploitation of women’s labor, demanding a feminist rethinking of value, labor, and development.